Leaving India : my family's journey from five villages to five continents - Hajratwala, Minal (Boston : Houghton Mifflin Harcourt, 2009)
"As the daughter of immigrants and the granddaughter of weavers, Minal Hajratwala grew up accustomed to crossing lines. In this work, she weaves together history, memoir, and reportage to explore questions facing not only her own family but that of every migrant: Where did we come from? Why did we leave? What did we lose and gain? Traveling the world, she learns how her family, originally from India, came to be spread across five continents and nine countries over more than a century of migration - a movement tht parallels the phenomenal growth of India's diaspora."--BOOK JACKET.
1. Water -- Pt. 1. "Coolies" -- 2. Cloth -- 3. Bread -- Pt. 2. Subjects -- 4. Salt -- 5. Story -- Pt. 3. Citizens -- 6. Brains -- 7. Shelter -- 8. Body -- Pt. 4. Destiny.
Includes bibliographical references (p. 405-416) and index.
Keywords: Hajratwala, Minal; Hajratwala, Minal -- Family; Gujarati Americans -- Biography; Children of immigrants -- United States -- Biography; Immigrants -- United States -- Biography; Gujaratis (Indic people) -- Biography; Immigrants -- Biography; East Indians -- Migrations -- Case studies; Emigration and immigration -- Psychological aspects -- Case studies; India -- Emigration and immigration -- Psychological aspects